Causal attribution and emotion in the days following competition - Allen, M. S.; Jones, M. V.; Sheffield, D. (Journal of Sports Sciences, 2009)
We examined the extent to which attributions are consistent in the days following competition and how attributions made immediately after competition may influence the temporal patterning of emotions experienced in response to competition. A sample of 60 adult female golfers completed measures of performance satisfaction, causal attribution, and emotion immediately after competition, 5 h after competition, and 2 days after competition. Repeated-measures multivariate analysis of covariance indicated that attributions did not change over this period. Emotions showed a significant decrease in intensity over the 5-h post-competition period. Regression analyses indicated that changes in anger and dejection were more likely in the case of less successful performances. For anger, attributions moderated this level of change. Golfers experienced anger for a longer period when they identified the cause of poor performance as stable rather than unstable. Thus, in the present sample although attributions did not change over 2 days, the longevity of anger depended on the attributions made immediately after competition.